2020
DOI: 10.1371/journal.pone.0241247
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported long-term benefit with an active transcutaneous bone-conduction device

Abstract: Purpose To evaluate the long-term benefits in hearing-related quality of life, patient satisfaction and wearing time of patients rehabilitated with an active transcutaneous bone-conduction device. Adverse events and audiological outcomes are reported as secondary outcomes. Methods This retrospective, mono-centric cohort analysis involves 16 adults with conductive or mixed hearing loss with a mean device experience of 51.25 months. Patient-reported outcome measures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Full text review of these 290 articles was conducted, and a total of 52 articles were selected for inclusion (Fig. 1) (13–64). Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Full text review of these 290 articles was conducted, and a total of 52 articles were selected for inclusion (Fig. 1) (13–64). Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An overview of the search process can be found in Figure 1. Descriptive features of articles about atresia surgery can be found in Supplemental Content 2, http://links.lww.com/MAO/B684 (9,10,18–52), and descriptive features of articles about implantable devices can be found in Supplemental Content 3, http://links.lww.com/MAO/B685 (8,10,22,43,47,48,53–99). All articles selected for inclusion were at least level 4 based on Oxford Level of Evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Full-text review of these 133 articles was conducted, and a total of 56 articles were selected for inclusion (Fig. 1) (11–14,21–72). Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Fig.…”
Section: Resultsmentioning
confidence: 99%